Sustainable Transformation of Rainfed to Irrigated Agriculture Through Water Harvesting and Smart Crop Management Practices - Jaramillo, Santiago; Graterol, Eduardo; Pulver, Edward (Frontiers in Sustainable Food Systems, 2020)
Globally, rainfed crop yields are about 50% lower than yields obtained under irrigated conditions. The low productivity of rainfed agricultural systems is the main factor that accentuates hunger, poverty, unemployment, and illegal migration in Central America and other regions in Latin America. Because of rainfall dependence, farmers can cultivate their crops during only one growing season per year, with high vulnerability to periodic droughts and flooding. To face the challenge of a sustainable food supply in the context of increasing food demand, since the mid-2000s, FLAR (Latin American Fund for Irrigated Rice), a public-private alliance of organizations from 17 Latin American countries CFC (Common Fund for Commodities), and CIAT (International Center for Tropical Agriculture) have been investing resources and efforts to sustainably intensify and diversify high-risk rainfed production systems through capturing runoff rainwater in reservoirs to transform those systems into highly profitable irrigated systems. This article summarizes concepts, results, and experiences from pilot farms using water harvesting in Nicaragua and Mexico, where irrigation combined with smart crop management practices allowed small-/medium-scale farmers to increase their yields of rice, maize, beans, and high-value crops by two to four times in comparison with historical yields obtained under rainfed conditions.